ISSUES OF DIGITALIZATION OF CARGO INSURANCE BASED ON BLOCKCHAIN TECHNOLOGIES AND ITS IMPORTANT ASPECTS - Hamrokulov Bahodir Mamasharifovich; Shoymardonova Mushtariybegim Alisher kizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Annotation: In this article, the digitization of cargo insurance in the insurance industry, reasons for digitization, a general understanding of blockchain technology, SWOT analysis of blockchain technology, practical examples of cargo insurance through blockchain technology and the implementation of this technology in Uzbekistan are discussed.